(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
Sector and spatial development in rural and urban regions of Namibia following in the wake of e.g. urbanisation, migration or mining – in essence often irreversible land consumption – call for an instituted physical organisation of space with the assistance of intra-national and trans-frontier strategies. Spatial planning perceived as an administrative technique and a comprehensive multi-disciplinary approach to balanced distribution of avenues to means of production-, the author exemplifies scientific foundations along with administrative conditions in practice and local situations of concern. In support of the ‘The Inaugural Namibian Conference on Strategic Spatial Planning for Urbanisation’ (2012), the paper ultimately promotes the joint and expanded furthering of ‘human capacity building’ through education and training at institutions of tertiary education in conjunction with departments of professional public sector and private sector planning agencies.